Climatology of thunderstorm activity over the Indian region : III. Latitudinal and seasonal variation (MAUSAM, 2005)
Knowledge of frequencies of occurrence of thunderstorms over Indian region is an issue of prime importance in the context of understanding of Indian southwest monsoon. To meet with this important need, we have examined climatological data of monthly mean number of thunderstorm days (Thn) as well as those of surface maximum air temperatures (Tmax) for 276 Indian observatory stations in this study and the results alt presented. Thn data have  been analyzed to describe their monthly latitudinal (7° N - 33° N) variation over India and the results are discussed in details. Seasonal variation of Thn and Tmax, averaged over 11 latitude ranges of 11 geographic regions of India, is also described. In this analysis, results of variation of Tmax and Thn within and outside the tropics are discussed. These two parameters showed systematic sequence in their phase shift as well as in their behavior of double/single oscillation  across the Indian range of latitudes over the course of annual period. More importantly, Thn data over 11 geographic regions have also been used to obtain their average score per station per each of the 11 geographic regions of India for the four seasons and for annual period. It is considered that this information may be useful for the identification of prime zones of high Thn activity in different parts of India. In meeting with the problems of lightning strikes and related issues this information could be of much value.